Pengaruh Sikap Berprilaku dan Motivasi Diri Terhadap Kinerja Karyawan Pada PT. Bank Danamon Indonesia - Ulta Rastryana; Usran Masahere (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
A corporation seeks optimal performance from its workforce, prompting researchers to conduct a study at the national private bank, PT. Bank Danamon Indonesia, situated on Jalan Prapatan Raya No. 50 in Central Jakarta. The study focuses on two independent variables, namely behavioral attitude and Internal drive. This study seeks to evaluate the influence of behavioral attitudes. and Internal drive on workplace productivity at PT. Bank Danamon Indonesia, Tbk Prapatan Raya Branch, Central Jakarta. The sample comprises all 68 employees at PT. Bank Danamon Indonesia, Tbk, Prapatan Branch. The researchers conducted various statistical analyses, including tests of validity, tests of reliability, tests for classical assumptions, t-tests, and f-tests, and regression analysis involving several variables analyses. The classical assumption test results indicate that each indicator in the independent and dependent variables is valid and reliable. In the t-test, both behavioral attitude and self-motivation variables individually influence employee performance variables significantly (with a sig value <0.05). Meanwhile, the f-test shows that both behavioral attitude and self-motivation variables collectively have a significant impact on workplace productivity variables (with sig < 0.05). This study yields positive influence results, suggesting that positive employee behavior and motivation correlate positively with employee performance.